Extase sans savoir et écriture de l’extase (France, xviie siècle) - Clément Duyck (Les Dossiers du GRIHL)
Ecstasy without Knowledge and Writing of Ecstasy (France, 17th century). How can the assertion of an ecstasy devoid of the activity of intelligence and memory, be consistent with writing practices meant to bear witness to such an ecstasy? Indeed, the traditional configuration of ecstasy without knowledge, in the context of the emergence in the Early Modern period of a mystical literature revolving around personal “experience”, is doubly problematic: it questions both the transcendental conditions of mystical knowledge, and the mere possibility of a writing that would not rely upon the knowledge of what it deals with. In this paper we will discuss three solutions, namely psychological, lyrical, and narrative, brought to the problem of ecstasy without knowledge during the French 17th century, emphasizing the originality of the literary solutions in comparison to the philosophical and theological treatments of the same issue.